Identifikasi Faktor Kurang Berjalannya TPS3R Citepus di Pasawahan Dayeuhkolot Kabupaten Bandung - Kania Sephiya Sunardi; Lely Syiddatul Akliyah (Jurnal Riset Perencanaan Wilayah dan Kota, 2023)
Abstract. The 3R Temporary Disposal Site (TPS) in Citepus, Pasawahan Village is a solution to the problem of waste by the community, but in reality, many problems occur such as the ineffectiveness of the 3R Temporary Disposal Site (TPS). So it is necessary to identify the factors that are not working properly at the 3R Temporary Disposal Site (TPS) in Citepus by identifying variables and supporting aspects to find out the factors that are not working properly at the 3R Temporary Disposal Site. This study used a quantitative descriptive analysis method by looking at the percentage of trends in the data and then comparing the existing conditions of the 3R Temporary Disposal Site. There are many variables obtained to identify factors that are not working at the Citepus 3R Temporary Disposal Site. Based on the identification results, 8 causal variables out of 13 variables are found that are not in accordance with their proper function, such as increasing the volume of waste residue, decreasing the volume of organic waste, no waste utilization, the location of the Temporary Disposal Site entering the flood area, no use of waste processing equipment, lack of waste management human resources, unfulfilled operational maintenance costs and no community involvement in management. The ineffectiveness of waste management at Temporary Disposal Sites is caused by the ineffectiveness of the 3R concept, which should be the core of the management carried out. Abstrak. TPS 3R Citepus Kelurahan Pasawahan disebut sebagai solusi dari permasalahan persampahan oleh masyarakat namun, kenyataannya banyak masalah yang terjadi seperti kurang berjalanya TPS 3R sehingga menjadikan tidak berjalannya konsep 3R pada TPS tersebut. Maka dari itu perlunya mengidentifikasi faktor kurang berjalannya TPS 3R Citepus dengan mengetahui variabel dan aspek pendukung untuk mengetahui indikator dalam hal faktor kurang berjalannya TPS 3R. Penelitian ini menggunakan metode analisis deskriptif kuantitatif dengan melihat persentase kecenderungan data kemudian membandingkan ketentuan eksistingnya yaitu TPS 3R. Terdapat banyak variabel yang didapatkan untuk mengidentifikasi faktor kurang berjalannya TPS 3R Citepus, Berdasarkan hasil identifikasi didapatkan 8 variabel penyebab dari 13 variabel yang tidak sesuai dengan fungsi TPS 3R yang seharusnya, seperti meningkatnya volume residu sampah, menurunya volume sampah organik, tidak adanya pemanfaatan sampah, lokasi TPS masuk kedalam kawasan banjir, tidak adanya penggunaan alat pengolah sampah, kurangnya SDM pengelola sampah, belum terpenuhinya biaya pemeliharaan operasional dan tidak adanya keterlibatan masyarakat dalam pengelolaan. Kurang berjalannya pengelolaan sampah di TPS diakibatkan tidak berjalannya konsep 3R, yang dimana seharusnya konsep tersebut menjadi inti dari pengelolaan yang dijalankan.